How bad do you want it? : mastering the psychology of mind over muscle - Fitzgerald, Matt (Velopress, 2015)
"Fitzgerald puts you into the pulse-pounding action of more than a dozen epic races from running, cycling, triathlon, XTERRA, and rowing with thrilling race reports and revealing post-race interviews with the elites. Their own words reinforce what the research has found: strong mental fitness lets us approach our true physical limits, giving us an edge over physically stronger competitors. Each chapter explores the how and why of an elite athlete's transformative moment, revealing powerful new psychobiological principles you can practice to flex your own mental fitness."--